Psychiatric diagnosis in attempted suicide - Sanjush Baby , Manju..P.Haridas & K .F.Yesudas (Calicut Medical Journal 2006;4(3):e2, 2006)
This is a retrospective study which assesses the various socio-demographic correlates, the methods adopted to commit suicide and the psychiatric disorders in patients attempting suicide. The most common psychiatric diagnosis was found to be Adjustment disorder followed by Depressive disorder. Organo-phosphorous compounds were the most frequent agent used among suicide attempt patients.